2007
DOI: 10.1016/j.ejvs.2006.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Mobility in Patients with Venous Leg Ulceration

Abstract: Mobility patterns among patients with leg ulcers are not significantly different to age matched controls. Ulcer patients take fewer steps per week compared to controls indicating they have reduced calf muscle pump function. Further studies are required to determine whether therapies which increase calf muscle activity have a role in ulcer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…ClarkeMoloney et al also reported that mobility patterns among patients with venous leg ulcers were not significantly different from the mobility patterns in age-matched controls; however, patients with ulcers took fewer steps per week. 21 We could not find any relation between onset-to-visit time or immobility status and clinical severity. However, many patients could not remember exactly when they started to have leg edema, and also we did not know exactly how they were living at home.…”
Section: Pathophysiology Of Leg Edema In Immobile Patientsmentioning
confidence: 53%
“…ClarkeMoloney et al also reported that mobility patterns among patients with venous leg ulcers were not significantly different from the mobility patterns in age-matched controls; however, patients with ulcers took fewer steps per week. 21 We could not find any relation between onset-to-visit time or immobility status and clinical severity. However, many patients could not remember exactly when they started to have leg edema, and also we did not know exactly how they were living at home.…”
Section: Pathophysiology Of Leg Edema In Immobile Patientsmentioning
confidence: 53%
“…[17,22,69,92,118] have all been monitored by accelerometry in clinical and non-clinicalbased studies. Many studies involving these groups have been accelerometry validation studies, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The monitor also provides data for energy expenditure (MET.hours, Physical Activity Level (PAL), kCAL) that is derived from the activity parameters; however, these have not been independently validated. The activPAL TM has been used for various clinical studies involving prosthetics and lower limb amputees [108][109][110], back pain [111], osteoporosis [112], cerebral palsy [113], the elderly [114][115][116], cardiology [117], venous ulceration [118], stroke [119] and motoric subtyping of delirium [27].…”
Section: Activpal Tm Professionalmentioning
confidence: 99%
“…A more recent application of portable NMES under realtime control is NMES blood flow assist [11][12][13]. These studies indicate that NMES may prove useful in the treatment of patients with venous ulceration who have reduced mobility or reduced ankle range movements.…”
Section: Introductionmentioning
confidence: 99%